Is it just? - Smith, Minnie (University of Toronto Press, 2011)
In Is It Just?, the conventions of the domestic novel - episodic presentation, stock characters, contrived plots, and romantic conclusions - illustrate the superiority of female values and argue for expanded social, political, and legal rights for women. A critical introduction by Jenny Roth and Lori Chambers frames Smith's specific references to the laws and social geography of British Columbia, situating the novel in relation to its historic and literary importance. This unique work of domestic literature adds to our limited library of Canadian feminist writings of the first wave."--Pub. desc.